INNOVATION DIFFUSION IN HEALTH SERVICES : EVALUATING INDONESIA’S PICK SICK GO HOME HEALTHY’ APPROACH - Novliza Eka Patrisia; Hardi Warsono; Kismartini Kismartini; Reni Shinta Dewi (Proceeding B-ICON, 2023)
This article aims to describe and qualitatively analyze the diffusion of healthcare service innovations in the "jemput sakit pulang sehat" (homecoming healthy patient pickup) healthcare service in the city of Bengkulu. Drawing from the Diffusion of Innovations theory, this study utilizes one of its elements, knowledge, in conjunction with the Theory of Reasoned Action (TRA) to understand the behavior involved in the delivery and implementation of healthcare services, aimed at enhancing the quality of public services in Bengkulu. This research employs a qualitative descriptive approach, with data sources including interviews, direct field observations, and documentation. The findings of this study highlight the significance of knowledge as the foundation for the diffusion of healthcare service innovations. The results are expected to provide valuable insights for the local government of Bengkulu, particularly the Bengkulu City Health Office, which is responsible for providing healthcare services. Through the dissemination of knowledge among all relevant stakeholders, it is anticipated that they can play their respective roles in innovation diffusion, ultimately leading to the improvement of healthcare service quality through effective and efficient service delivery, with a focus on innovation objectives.